Development of a friendlier chemical process framework using the inherent safety concept / Gao Xiaoming - Gao , Xiaoming (2022)
To date, inherent safety concept has been regarded as the most robust solution for risk management and loss prevention in chemical processes. Its proactive interventions of building safety measures into the process design schemes can avoid adding extensive end-of-pipe protections when the processes evolve to the operation stage. In practice, numerous frameworks have been presented to develop inherently safer process routes. Together with the inherent Safety (S) framework, various dedicated assessment tools for designing inherent Health (H) and Environmentally (E) benign chemical process routes have been proposed to eliminate or minimize the SHE risks at the design stage. However, the dedicated inherent SHE assessment tools give limited attention to the weights and uncertainties of the component indicators. Also, whether the incremental costs of implementing "inherent" principles can distort the overall process friendliness is yet to be demonstrated. To bridge the gaps, this study weighted and reconciled the separate inherent SHE metrics with cost indices considering the risk uncertainties, thus developing a novel Reconciled Friendly Process Framework (RFPF) to realize inherently Friendlier Chemical Processes (FCP). The FCP are characterized to be inherently safer, healthier, and more environmentally benign with tradeoff considerations on the incremental costs of design modifications. To develop the RFPF and realize the FCP, the pioneering Inherent Safety Index (ISI), Inherent Occupational Health Index (IOHI), Inherent Environmental Toxicity Hazard (IETH), and Inherent Safety Implementation Cost (ISIC) were selected and adapted to indicate the inherent friendliness features. Subsequently, the selected inherent friendliness indicators were weighted using Analytic Hierarchy Process (AHP) method and reconciled using the fuzzy logic and Bayesian Networks (BN). Lastly, the newly developed RFPF was validated by a case study of biodiesel production processes. The results show that the inherent friendliness of the Baseline Design Processing Option (BDPO) was estimated as Moderate (M) level (inherent friendliness ≈ 3.05), while it improved to Relatively Friendly (RF) level (inherent friendliness ≈ 2.28) after implementing inherently friendlier modifications. The significant improvement of the inherent friendliness implies that the Modified Design Processing Option (MDPO), compared with the BDPO, can be a more reliable option with fewer built-in SHE risks under the incorporated incremental costs. The newly developed RFPF synthesized the conflicting factors of SHE and cost indices with weights and normalized risk scores to develop inherently FCP during the process design stage, which can be expected to use as a more realistic tool to proactively, fundamentally, and economically reduce the SHE risks at their sources.